Cultural Ethnography of Pecel Madiun: Reconceptualizing Civic Spaces for National Character Formation - Yoga Ardian Feriandi; Risti Aulia Ulfah; Ary Purwatiningsih (ASANKA : Journal of Social Science and Education, 2026)
This study aims to analyze the role of traditional cuisine as a medium for lived citizenship in the formation of national character. Utilizing a qualitative approach with a focused ethnography design, this research was conducted at warung pecel (traditional food stalls) in Madiun City from December 2025 to January 2026. Data were gathered through focused observation, in-depth interviews, and visual documentation, which were then analyzed inductively through the lenses of the sociology of citizenship and public space. The results indicate that warung pecel functions as an egalitarian and inclusive civic space imbued with citizenship values. Social practices such as communal seating regardless of social class, the ethics of "geser-geseran", fair queuing, the use of pincuk, and informal public discourse manifest social citizenship, cultural nationalism, and ecological awareness in everyday life. This study concludes that citizenship and national character are not solely constructed through formal education and legalistic approaches, but also through grounded, repetitive cultural practices. The implications of this research underscore the need to reconceptualize learning resources for Pancasila and Civic Education by leveraging local cultural spaces as social laboratories for citizenship.